A child born to immigrant parents at Lepenski Vir - Maxime Brami; Jens Blöcher; Yoan Diekmann (Documenta Praehistorica)
Our 2022 article challenged the traditional view of Lepenski Vir as a Mesolithic village that became Neolithic. Instead, genetic analysis suggests it was founded by Aegean farmers who occasionally admixed with local hunter-gatherers but maintained separate burials. New genomes released by Žegarac et al. (2025), including that of an infant boy with fully Aegean ancestry during the final phase of occupation, support the presence of entire immigrant families at the site. The discovery of neonates of mixed ancestry beneath house floors highlights complex interactions during the transitional phase. Additional kinship and identity-by-descent analyses offer deeper insight into early farmer-forager admixture processes.